Relating Factors to Stress Levels in Elderly People with Hypertension - Andi Suswani Makmur; Aszrul AB; Sri Wahyuningsi (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
Background; Stress in most elderly people is caused by gradual physical and psychological decline, which can cause psychosocial problems in the form of depression and anxiety. Stress can trigger the hormone adrenaline so that the heart pumps faster resulting in increased blood pressure. Objective: The general objective of this research is to determine the factors related to stress levels in elderly people with hypertension in the Balibo Community Health Center working area, Bulukumba Regency. Method: This research is a quantitative study with a cross-sectional research design. The sample in this study was 61 respondents using random sampling technique. Data collection uses a questionnaire. Results: this research shows that there is a relationship between economic level and stress level with a value of p= 0.012 (p>0.05), there is a relationship between physical condition and stress level with a value of p=0.018 (p>0.05), and There is a relationship between the level of independence and the level of stress with a value of p=0.038 (p>0.05). Conclusion: From the results of the research it can be concluded that there is a relationship between economic level, physical condition and level of independence on stress levels in elderly people with hypertension in the Balibo Community Health Center Work Area in 2023.